Response of Foliar Application of Nano Fertilizers on Growth and Yield of Maize (Zea mays L.) in South-West Rajasthan - Khardia, Neha; Meena, R. H.; Kumar, Manoj; Sharma, Sonal; Kumawat, Hansa; Salvi, Kartik; Meena, Deshraj (International Journal of Economic Plants, 2024)
A field experiment was conducted during kharif 2020 (June–October) at Instructional Farm of Agronomy, Rajasthan College of Agriculture, Udaipur to study the effect of foliar application nano fertilizers (N, Zn and Cu) on growth and yield of maize crop. The experiment was laid out in randomized block design with three replications and twelve treatments. The foliar application of tricombinations (nano N+nano Zn+nano Cu) of nano fertilizers along with 50% recommended dose of N and Zn plus 100% PK through conventional fertilizers i.e.,100% PK+50% N Zn+two sprays of nano N+nano Zn+nano Cu (T12) significantly increased seed yield (4482.2 kg ha-1) and stover yield (7994.81 kg ha-1) by inducing the growth parameters i.e., the plant height (260.44 cm), dry matter accumulation (154.85 g), cob length (23.65 cm), number of grains per cob (346.7), weight of cob (159.33 g), weight of 100 seeds (24.92 g) of maize over control. However, the application of T12 were found statistically at par with 100% PK+50% N Zn+two sprays of nano N+nano Zn (T11) in growth and yield of maize. Based on these results, the application 100% PK+50% N Zn+two sprays of nano N+nano Zn can be recommended for higher maize productivity in Sub-humid Southern Plains and Aravalli Hills of Rajasthan.